Integrated analytical system in the monitoring of carboniferous mine wastes from the "Bogdanka" hard coal mine = Zintegrowany analityczny system w monitoringu karbońskich odpadów wydobywczych z kopalni węgla kamiennego "Bogdanka" (Lubelskie Zagłębie Węglowe) - Bzowski, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In order to evaluate usefulness of wastes for utilization it is necessary to use modern chemical testing methods. The proposed analytical system of the XRD-XRF-ICP-GC methods enables to conduct an examination of carboniferous waste rocks. The offered system of chemical testing is less time consuming and much more efficient.
Keywords: monitoring; zintegrowany układ analityczny; odpady wydobywcze; kopalnia węgla kamiennego; analytical system; carboniferous coal wastes